Deník Heleny Hanžlové: (České Budějovice v lednu až červnu 1945) - Petráš, Jiří (Lidé města, 2007)
In recent years, the professional historical production has been trying to catch up with belles-lettres regarding its quality and abundance. To depict life of an ordinary person means to use sources not yet exploited, to look at history from a different vantage point, and be ready to employ new historical methods. Researchers interested in the latest history have, compared to others, one additional significant comparative advantage – they can use living human being, a narrator, as a source. Resulting works peer under the surface of things, depicting contemporary atmosphere and mood through a real person. In recent years, the Oral History Center of the Institute for Contemporary History of the Academy of Sciences in Prague comes with interesting impulses. However, its projects and primarily the results have for now – unfortunately – more response abroad. Regional historiography plays an important role in this area. As if its representatives, historians knowing the environment they cover and people living there, are closer to life. They can also use many sources which others leave unnoticed in museums, archives and elsewhere. The following written records, dated 1945, used as the bases for this work are of museum provenience. These records, written by an unknown female hand immediately at the time that they depict, were donated to the museum in 2004. The author had an opportunity to employ the above mentioned oral history method. Confrontation of written records and oral recollections – although few decades later – is clearly suggested, just like it is important to get to know their originators including their opinions, discover what development of thought they experienced and how they look back on their life years later. And that is the story of the following text, story of Helena Hanžlova’s diary and story of the citizen Helena Hanžlova.